Knowledge of adolescent students about HIV/AIDS - Rebeca Coelho de Moura Angelim; Fátima Maria da Silva Abrão; Luciana da Rocha Cabral; Síngara Borba de Araújo Queiroz; Rafaela Marrise do Monte Freitas; Mirian Domingos Cardoso (Universidade Federal de Santa Maria, 2015)
Aim: to verify the knowledge of adolescent students about HIV/AIDS. Method: exploratory descriptive study with quantitative approach, conducted with 298 students from two public schools of Recife, Pernambuco, Brazil. A self-administered questionnaire was used for data collection. Results: the study points out that most teenagers already initiated sex life (53.4%); regarding preventive methods, 44.1% reported having used them, condoms being the most frequent. Most students (92%) reported knowing the HIV/AIDS transmission routes. Television was the main source of information about HIV/AIDS. Conclusion: despite having knowledge about HIV/AIDS transmission, that doesn't mean that the adolescents perform safe sexual practices, thus, there is a need to implement policies of health promotion and protection in the school environment